The Novel Marker GATA3 is Significantly More Sensitive Than Traditional Markers Mammaglobin and GCDFP15 for Identifying Breast Cancer in Surgical and Cytology Specimens of Metastatic and Matched Primary Tumors. Issue 4 (April 2016) - Sangoi, Ankur R.; Shrestha, Bijayee; Yang, George; Mego, Ourhay; Beck, Andrew H.
Abstract : Traditional markers mammaglobin and GCDFP15 show good specificity but lack sensitivity and can be difficult to interpret in small tissue samples. We undertook a comparative study of the novel nuclear marker GATA3 (expression typically restricted to breast and urothelial carcinomas) and GCDFP15 and mammaglobin. We first compared quantitative mRNA expression levels of these 3 markers across a diverse set of over 6000 tumors and 500 normal samples from The Cancer Genome Atlas which showed dramatically higher GATA3 expression (>10-fold higher) in breast cancer as compared with GCDFP15 or mammaglobin (both P <2.2e−16), suggesting that GATA3 may represent a more sensitive marker of breast cancer than GCDFP15 or mammaglobin. We next examined protein expression by immunohistochemistry in 166 cases (including surgical and cytology specimens) of metastatic breast carcinoma and 54 cases with available matched primaries. One whole-slide section from each case was stained for monoclonal GATA3 (L50-823), monoclonal mammaglobin (31A5), and monoclonal GCDFP15 (EP1582Y). Staining intensity (0 to 3+) and extent (0% to 100%) were scored with an H -score calculated (range, 0 to 300). Sensitivities by varying H -score cutoffs for a positive result in metastatic breast carcinoma among GATA3/GCDFP15/mammaglobin, respectively, were as follows: any H -score=95%/65%/78%, H -score>50=93%/37%/47%, H -score>100=90%/25%/27%, H -score>150=86%/21%/19%, H -score>200=73%/18%/9%, H -score>250=66%/14%/6%. Significant staining differences by specimen type, tumor subtype/grade, or ER/PR/HER2 status were not identified. Significantly stronger correlation was observed between primary/metastatic GATA3 expression [Pearson's correlation=0.81 (0.68-0.89)] as compared with the primary/metastatic correlations of GCDFP15 [Pearson's correlation=0.57 (0.33-0.74)] and mammaglobin [Pearson's correlation=0.50 (0.24-0.70)] (both P <0.05). In conclusion, the novel marker GATA3 stains a significantly higher proportion of both primary and metastatic breast carcinomas than GCDFP15 or mammaglobin with stronger and more diffuse staining, helpful in cases with small tissue samples. The matched primary/metastatic expression of GATA3 is also more consistent. We propose that GATA3 be included among a panel of confirmatory markers for metastatic breast carcinoma.